Stagnacja, ewolucja czy rewolucja. Ustrój Polski między 13 grudnia 1981 a 4 czerwca 1989 r. Mity i fakty - KOSMAN, Marceli (Przegląd Politologiczny, 2018)
The paper concerns the syncretistic, evolutionary nature of political transformation in Po- land prior to the introduction of political plurality in mid-1989. The author refers to the studies published in his books: Wojciech Jaruzelski wobec wyzwañ swoich czasów [Wojciech Jaruzelski and the challenges of his time] (2003) and Los genera3a [The General’s fate] (2008) where he confronts recorded facts with political propaganda. The evolution which eventually led to political plurality occurred in three stages. The first spanned the period ending when martial law was formally revoked after 586 days (on July 22, 1983), the second one was related to the office of Prime Minister that Wojciech Jaruzelski held (until September 25, 1985), and the third stage commenced when he gave up direct supervision of the government and assumed the office of Head of State (which continued to be combined with the actual power he held as 1st secretary of the Central Committee of the Polish United Workers’ Party (KC PZPR)). The last stage was to continue for nearly four years, excluding over 18 months of his presidency, held under completely different conditions. Yet these 18 months were significant for the evolutionary process of the handover of power. Jaruzelski took into consideration the international context, particularly the balance of power in the Kremlin. Real change took place there only after Mikhail Gorbachev assumed power on March 11, 1985. On May 29, 1985 the Polish parliament passed the law on the Constitutional Tribunal, announced three years earlier in an amendment to the Constitution of March 1982. On July 15, 1987 the parliament passed the law on the Defense of Human Rights. The State Tribunal began working at the same time. The first president of Poland after the transformation drew attention to these facts a few years later. The ex-President has become a skilful polemicist and political writer, documenting the peaceful political transformation in Poland after 1980.